Investigating Cardiac MRI Based Right Ventricular Contractility as a Novel Non-Invasive Metric of Pulmonary Arterial Pressure. Issue 8 (January 2014) - Menon, Prahlad G.; Adhypak, Srilakshmi M.; Williams, Ronald B.; Doyle, Mark; Biederman, Robert W. W.
Background: We test the hypothesis that cardiac magnetic resonance (CMR) imaging-based indices of four-dimensional (4D) (three dimensions (3D) + time) right ventricle (RV) function have predictive values in ascertaining invasive pulmonary arterial systolic pressure (PASP) measurements from right heart catheterization (RHC) in patients with pulmonary arterial hypertension (PAH). Methods: We studied five patients with idiopathic PAH and two age and sex-matched controls for RV function using a novel contractility index (CI) for amplitude and phase to peak contraction established from analysis of regional shape variation in the RV endocardium over 20 cardiac phases, segmented from CMR images in multiple orientations. Results: The amplitude of RV contractility correlated inversely with RV ejection fraction (RVEF; R 2 = 0.64, P = 0.03) and PASP ( R 2 = 0.71, P = 0.02). Phase of peak RV contractility also correlated inversely to RVEF ( R 2 = 0.499, P = 0.12) and PASP ( R 2 = 0.66, P = 0.04). Conclusions: RV contractility analyzed from CMR offers promising non-invasive metrics for classification of PAH, which are congruent with invasive pressure measurements.